Analisis Perilaku Konsumen Muslim yang Melakukan Transaksi Real Money Trading - Abdurrafi Muhammad Azra; Nanik Epriyanti; Zia Firdaus Nuzula (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Technological developments are increasingly rapidly impacting aspects of public entertainment, such as online games such as Mobile Legends. One of the users is the 2018-2020 Sharia Faculty student. Facts in the field are still found by students who carry out Real Money Trading transactions excessively. Whereas in Islam a Muslim should apply the principles of consumer behavior in accordance with Islamic teachings. The aim of the research is to analyze how consumption behavior is according to Islam and how consumption behavior is carried out by students of the Faculty of Sharia class 2018-2020 when carrying out Real Money Trading transactions according to Islam. The benefits of research as a reference in applying the principles of Muslim consumer behavior that must be carried out by a Muslim and as a reference regarding the principles of Muslim consumer behavior. This study used qualitative methods, data field research types, primary and secondary data sources, questionnaire data collection techniques, literature studies, observations and interviews. The results of the first author's research should be that a Muslim when carrying out consumption activities applies the 5 principles of Muslim consumers and aims to get blessings for life in the hereafter. Second, with a percentage of 66% of the 2018-2020 class of Sharia Faculty students having applied the principles of Muslim consumer behavior when conducting Real Money Trading transactions, there were still 34% of students who had not applied the principles of Muslim consumer behavior when conducting Real Money Trading transactions and did not do the principle of simplicity. Abstrak. Perkembangan teknologi makin pesat berdampak pada aspek hiburan masyarakat, seperti terdapat permainan online seperti Mobile Legends. Salah satu penggunanya mahasiswa Fakultas Syariah 2018-2020. Fakta dilapangan masih ditemukan mahasiswa yang melakukan transaksi Real Money Trading dengan berlebihan. Sedangkan dalam islam seorang muslim hendaknya menerapkan prinsip perilaku konsumen yang sesuai dengan ajaran islam. Tujuan penelitian untuk menganalisis bagaimana perilaku konsumsi menurut islam dan bagaimana perilaku konsumsi yang dilakukan oleh mahasiswa Fakultas Syariah angkatan 2018-2020 ketika melakukan transaksi Real Money Trading menurut islam. Manfaat penelitian sebagai acuan dalam menerapkan prinsip perilaku konsumen muslim yang harus dilakukan seorang muslim dan sebagai rujukan mengenai prinsip perilaku konsumen muslim. Penelitian ini menggunakan metode kualitatif, jenis data field research, sumber data primer dan sekunder, teknik pengumpulan data kuesioner, studi pustaka, observasi dan wawancara. Hasil penelitian penulis pertama hendaknya seorang muslim ketika melakukan kegiatan konsumsi menerapkan 5 prinsip konsumen muslim dan bertujuan mendapatkan berkah untuk kehidupan di akhirat. Kedua, dengan hasil persentasi sebesar 66% mahasiswa Fakultas Syariah angkatan 2018-2020 telah menerapkan prinsip perilaku konsumen muslim ketika melakukan transaksi Real Money Trading, namun masih ada 34% mahasiswa yang belum menerapkan prinsip perilaku konsumen muslim ketika sedang melakukan transaksi Real Money Trading dan tidak melakukan prinsip kesederhanaan.